2015
DOI: 10.3892/ol.2015.3534
|View full text |Cite
|
Sign up to set email alerts
|

Ewing's sarcoma of the ulna treated with sub-total resection and reconstruction using a non-vascularized, autogenous fibular graft and hernia mesh: A case report

Abstract: Ewing's sarcoma of the bone is the second most frequently occurring malignant bone tumor in children and adolescents. Ewing's sarcoma in the ulna are extremely rare. Thus, the surgical options for reconstruction of the elbow are limited and technically challenging. In the current study, a 29-year-old male with Ewing's sarcoma of the ulna was treated with a sub-total resection and reconstruction using a non-vascularized, autogenous fibular graft and hernia mesh. At the 2-year follow-up, the patient had returned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Megas et al (12) reported 20-110 0 of elbow ROM with 40-30 0 of prono-supination at more than 2 years follow-up with non-vascularized fibula in a case of metastatic carcinoma. However, the outcomes were superior when part of the olecranon was saved, and fibular graft was used as intercalary grafts (14,15). Wang et al (14) reported elbow ROM of 0-135 0 with 30-85 0 of prono-supination after intercalary fibular autograft.…”
Section: Resultsmentioning
confidence: 99%
“…Megas et al (12) reported 20-110 0 of elbow ROM with 40-30 0 of prono-supination at more than 2 years follow-up with non-vascularized fibula in a case of metastatic carcinoma. However, the outcomes were superior when part of the olecranon was saved, and fibular graft was used as intercalary grafts (14,15). Wang et al (14) reported elbow ROM of 0-135 0 with 30-85 0 of prono-supination after intercalary fibular autograft.…”
Section: Resultsmentioning
confidence: 99%
“…The main malignant bone tumors seen around the elbow are osteosarcoma, primary giant cell bone tumor, and Ewing sarcoma. (Wang and Lin, 2015). In our study, we presented a case of Ewing Sarcoma of 15-year-old female (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Reconstruction of the proximal ulna after wide tumor resection using a nonvascularized fibular autograft has been reported in only 3 patients 5, 7, 15. Goyal et al 5 treated a 15-year-old child with desmoplastic fibroma of the ulna, preserving the proximal half of the olecranon for firm fixation to the graft.…”
Section: Discussionmentioning
confidence: 99%
“…At 2 years of follow-up, the active ROM at the elbow was 40° to 130°. Similarly, Wang et al 15 performed a subtotal resection of the proximal ulna and subsequent reconstruction of the proximal portion of the intraosseous membrane with a hernia mesh in a 29-year-old patient with Ewing sarcoma. They reported an excellent functional outcome, with 0° to 135° elbow ROM and forearm pronation of 35° and supination of 85°at 2 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%